Membangun Budaya Organisasi di Lembaga Pendidikan Islam - Listiana Ayu Indarwati; Rifdah Auva Apriliana; Desti Meliana Ramandhani; Yusron Masduki (Prodi Pendidikan Keagamaan Islam, 2023)
Organizational culture can be interpreted as the integrity of the values, procedures or methods that are followed and can be created as a guide both individually and collectively in an organizational institution. The organization will pay attention to progress and development, if the organizational culture or habits in an organizational institution are organized and also run well. This study aims to examine in depth related to how to build an organizational culture in an Islamic educational institution. The method used in this study is the method of literature or library research. The results of the study show that an organization has a very important role for Islamic education institutions, namely related to student motivation and achievement, achievement of educational quality, as well as job satisfaction and teacher productivity. This is very appropriate to be used as a reference for educational organizations in an Islamic perspective to achieve a desired goal.